2001
DOI: 10.1080/000164801316878935
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine Fistula Detection: The Predictive Value of Vestibular Symptoms and Computerized Tomography

Abstract: A retrospective case record study of 20 patients in Oslo operated on for chronic otitis media with labyrinthine fistula between 1986 and 1999 was performed in order to estimate the incidence of, and identify predictors for, labyrinthine fistulas. The incidence of fistula was 0.3 per 100 000, with a median age at diagnosis of 37 years. The median duration of chronic otitis media prior to labyrinthine fistula detection was significantly correlated with age at surgery. Subjective hearing loss (90%), otorrhoea (65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 13 publications
1
34
1
2
Order By: Relevance
“…At 26 months follow-up, the patient had an average of 10 dB of bone conduction improvement at 0.5, 1, 2 and 4 kHz. Unlike other studies, our patient was much younger than what has been previously reported where the mean age vary from 37 to 56 years [6][7][8][9]. Cholesteatomas in children have a more aggressive growth pattern relative to adults [12][13][14].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…At 26 months follow-up, the patient had an average of 10 dB of bone conduction improvement at 0.5, 1, 2 and 4 kHz. Unlike other studies, our patient was much younger than what has been previously reported where the mean age vary from 37 to 56 years [6][7][8][9]. Cholesteatomas in children have a more aggressive growth pattern relative to adults [12][13][14].…”
Section: Discussioncontrasting
confidence: 74%
“…Of these, a second fistula on another SSC was present in 7-11% of cases [1,2]. Bony erosion and subsequent fistulas formation occurs most frequently in the lateral semicircular canal counting for nearly 90% of the cases of labyrinthine fistulas [1,3,6,8]. The prevalence of superior and posterior semicircular canal fistulas reported in the literature is respectively 6% and 2% [1,3,6,9].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Its incidence varies between 4 and 12%, with a predilection for the horizontal semicircular canal (SCC) representing 66-90% of Wstulas [1][2][3][4][5][6]. Hearing loss (90%), otorrhea (65%) and dizziness (50%) are the most frequent presenting symptoms [7]. Although history of disease and clinical examination are essential in diagnosing a labyrinthine Wstula, classical signs and symptoms associated with Wstulas are neither sensitive nor speciWc for the disease [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although history of disease and clinical examination are essential in diagnosing a labyrinthine Wstula, classical signs and symptoms associated with Wstulas are neither sensitive nor speciWc for the disease [8][9][10][11]. High-resolution computerized tomography (CT) scan included in the preoperative assessment of cholesteatoma allows a high rate of suspicion for labyrinthine Wstulas [1,7,9,12].…”
Section: Introductionmentioning
confidence: 99%